Cut-off values of lesion and vessel quantitative flow ratio in de novo coronary lesion post-drug-coated balloon therapy predicting vessel restenosis at mid-term follow-up. Issue 12 (20th June 2021) - Meng, Pei-Na; Liu, Bin; Li, Long-Bo; Yin, De-Lu; Zhang, Heng; Pan, De-Feng; You, Wei; Wu, Zhi-Ming; Wu, Xiang-Qi; Zhao, Lei; Li, Zhi-Bo; Wang, Jin-Peng; et al.
Abstract: Background: Drug-coated balloons (DCBs) have emerged as potential alternatives to drug-eluting stents in specific lesion subsets for de novo coronary lesions. Quantitative flow ratio (QFR) is a method based on the three-dimensional quantitative coronary angiography and contrast flow velocity during coronary angiography (CAG), obviating the need for an invasive fractional flow reserve procedural. This study aimed to assess the serial angiographic changes of de novo lesions post-DCB therapy and further explore the cut-off values of lesion and vessel QFR, which predict vessel restenosis (diameter stenosis [DS] ≥50%) at mid-term follow-up. Methods: The data of patients who underwent DCB therapy between January 2014 and December 2019 from the multicenter hospital were retrospectively collected for QFR analysis. From their QFR performances, which were analyzed by CAG images at follow-up, we divided them into two groups: group A, showing target vessel DS ≥50%, and group B, showing target vessel DS <50%. The median follow-up time was 287 days in group A and 227 days in group B. We compared the clinical characteristics, parameters during DCB therapy, and QFR performances, which were analyzed by CAG images between the two groups, in need to explore the cut-off value of lesion/vessel QFR which can predict vessel restenosis. Student's t test was used for the comparison of normally distributed continuous data, Mann-Whitney U test for the comparison of non-normally distributed continuous data, and receiver operating characteristic (ROC) curves for the evaluation of QFR performance which can predict vessel restenosis (DS ≥50%) at mid-term follow-up using the area under the curve (AUC). Results: A total of 112 patients with 112 target vessels were enrolled in this study. Group A had 41 patients, while group B had 71. Vessel QFR and lesion QFR were lower in group A than in group B post-DCB therapy, and the cut-off values of lesion QFR and vessel QFR in the ROC analysis to predict target vessel DS ≥50% post-DCB therapy were 0.905 (AUC, 0.741 [95% confidence interval, CI: 0.645, 0.837]; sensitivity, 0.817; specificity, 0.561; P < 0.001) and 0.890 (AUC, 0.796 [95% CI: 0.709, 0.882]; sensitivity, 0.746; specificity, 0.780; P < 0.001). Conclusions: The cut-off values of lesion QFR and vessel QFR can assist in predicting the angiographic changes post-DCB therapy. When lesion/vessel QFR values are <0.905/0.890 post-DCB therapy, a higher risk of vessel restenosis is potentially predicted at follow-up.